First-hand experience of why gamification projects fail and what could be done about it - Hassan, Lobna; Morschheuser, Benedikt; Alexan, Nader; Hamari, Juho (Proceedings of the 2nd International GamiFIN Conference, 2018)
A plethora of services, applications and scholarly research has emerged related to gamification. Regardless of the optimistic onset of this hype around the technology trend, designing gamification has proved to be a challenging endeavor; requiring multidisciplinary work that is often hindered by multiple theoretical and practical challenges. Problem-driven, theory-advancing approaches to gamification research could assist in the addressment of gamification design challenges and accelerate the growth of the gamification field however not all such approaches have been equally utilized or understood. This paper presents the case of MANGO: a project to design a gamified e-participation tool through Action Design Research (ADR). The paper reflects on the challenges of gamification design and development and possible strategies to address them. It additionally reflects on the ADR process; an under-utilized and hence possibly a superficially understood approach to gamification research. The paper is hence a guide for researchers and practitioners as to possible challenges they can face with gamification research and design and how to counteract them.<br
CRIS-Team Scopus Importer:2021-02-01